Distribution, Diversity and Ecological Characteristics of Freshwater Ostracoda (Crustacea) in Shallow Aquatic Bodies of the Ankara Region, Turkey - (:unkn) unknown (SPRINGER, 2014)
Although Turkey has a variety of wetlands of different types and sizes, many of them are threatened by human activities. To show the biological importance of these habitats, samples were randomly collected from 173 different wetland sites in the Ankara region during the summer of 2011. 31 ostracod taxa belonging to 14 genera were identified, including two species (Eucypris elliptica and Cavernocypris subterranea) that are new reports for the Turkish ostracod fauna and 19 taxa that are new reports for the region. Canonical Correspondence Analyses was able to show 58.9% of the correlation between species and environmental variables. Water temperature, moisture and dissolved oxygen were the most important (P = 0.05) factors influencing species occurrence. Increasing sampling size (number of sites) did not significantly increase the numbers of species collected at sites located at elevations between 442 and 1,520 m.a.s.l. This also implies that altitude may have a secondary role on species diversity. Unweighted Paired Group Mean Analyses illustrated four main clustering groups of ostracods, in which species are clustered according to their ecological preferences. Based on our results, suitability of habitats appears to drive ostracod distribution and diversity in these wetland sites. Results clearly showed that these habitats can harbor diverse ostracod communities that warrant conservation.
Keywords: Ostracods; Wetlands; Diversity; Ecological tolerance; Distribution; SPATIOTEMPORAL VARIABILITY; ALTITUDINAL RANGES; BOLU REGION; REQUIREMENTS; HABITAT; SPRINGS; LAKE; ASSEMBLAGES; DIYARBAKIR; MANAGEMENT